Analysis of Potential Hazards and Risk in Engineering, Procurement & Constructions Services Project for Deconstraint Facility Construction Using Failure Mode and Effects Analysis (FMEA) Method at PT Raga Perkasa Ekaguna (RPE) Duri, Riau - Arfiansyah, Deri; Setyowati, Ekaterina; Ramli, Soehatman (International Journal of Environmental, Sustainability, and Social Science, 2026)
The Deconstraint facility construction project is a process to install a new Water Injection System with a capacity of 100,000 BWPD, which is distributed through 2 (two) water injection headers at Grand Station and its supporting facilities. The purpose of this study is to assess the risk of potential hazards and risks that will occur if a failure occurs in the EPC process of the Deconstraint Facility Construction using the FMEA (Failure Mode and Effect Analysis) method. This research method uses descriptive-analytical with a qualitative and quantitative approach with data collection techniques using observation, interviews, and triangulation. The results of this study state the highest Risk Priority Number (RPN) value with a value of 100 (one hundred), which is in the failure of lifting and rigging during the installation of the pump caused by the failure of lifting equipment due to calculation errors while the lowest RPN value with a result value of 6 (six) is in the drawing and design making activities with the potential for failure is in errors in making the design that is made wrong. Controlling potential hazards and risks resulting from lifting equipment failures was explored through human, method, machine, and environmental factors. The conclusion of this study is that failures in lifting and rigging during pump installation, caused by miscalculations of the lifting equipment used, had the highest score.